1997
DOI: 10.1074/jbc.272.3.1608
|View full text |Cite
|
Sign up to set email alerts
|

Structural Domain Organization of Gastric H+,K+-ATPase and Its Rearrangement during the Catalytic Cycle

Abstract: Differential scanning calorimetry has been used to characterized the thermal denaturation of gastric (H ؉ ,K ؉ )-ATPase. The excess heat capacity function of (H ؉ ,K ؉ )-ATPase in highly oriented gastric vesicles displays two peaks at 53.9°C (T m1 ) and 61.8°C (T m2 ). Its thermal denaturation is an irreversible process that does not exhibit kinetic control and can be resolved in two independent two-state processes. They can be assigned to two cooperative domains located in the cytoplasmic loops of the ␣-subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 58 publications
(54 reference statements)
0
22
0
2
Order By: Relevance
“…However, we believe that the transmembrane fragments of the Na + /K + ‐ATPase are highly stable and do not contribute to the unfolding transition of this protein in the temperature range studied. Supporting this idea, no thermal transition has been observed in the proteolytically isolated membrane region of the H + /K + ‐ATPase homologous to the Na + /K + ‐ATPase [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we believe that the transmembrane fragments of the Na + /K + ‐ATPase are highly stable and do not contribute to the unfolding transition of this protein in the temperature range studied. Supporting this idea, no thermal transition has been observed in the proteolytically isolated membrane region of the H + /K + ‐ATPase homologous to the Na + /K + ‐ATPase [29].…”
Section: Discussionmentioning
confidence: 99%
“…Because much as the enthalpy of the third transition is dependent on ATP binding, one could suggest that it represents the large cytoplasmic loop. Remarkably, the cation occlusion and ATP binding sites have been assigned to two discrete folding domains of the α subunit in the homologous H + /K + ‐ATPase [29].…”
Section: Discussionmentioning
confidence: 99%
“…Gasset et al (30) observed two peaks of heat capacity at 53.9 and 61.8°C in gastric H,K-ATPase. We would have predicted that the heat transition at 53.9°C corresponds to the physical changes we observed at 55°C, but protection by K ϩ confounds this interpretation.…”
Section: Figmentioning
confidence: 99%
“…Yet, no quantitative determination of the size of the protein region affected by the changes has been made. Recent differential scanning calorimetry experiments show that arrangement of two distinct structural domains characterized by two temperature‐induced cooperative unfolding are present in the E1 conformation (Na + buffer) but that one disappears when the enzyme is forced into the E2 conformation (K + buffer) [11]…”
mentioning
confidence: 99%
“…One potential explanation for the vanishing transition in one of the protein domains is that this domain becomes embedded or partially embedded in the membrane [11]. The K + binding site has also been suggested to be on the H6 segment [12], a part of the H5‐H6 hairpin, accessible to trypsin cleavage in the absence of ligands but not in the presence of K + [13].…”
mentioning
confidence: 99%